Future of Software Test Automation Using AI/ML (International Journal of Engineering and Computer Science, 2025)
The exponential growth of software systems and the shift toward agile and DevOps methodologies have placed immense pressure on quality assurance teams to deliver rapid, reliable, and scalable testing solutions. Traditional test automation methods, while effective in some contexts, often struggle with adaptability, maintenance overhead, and limited intelligence in handling dynamic test environments. This paper investigates the transformative role of Artificial Intelligence (AI) and Machine Learning (ML) in shaping the future of software test automation.Through an in-depth analysis of academic literature, industrial case studies, and current tool capabilities, this study identifies the core AI/ML techniques being leveraged—such as predictive analytics, computer vision, reinforcement learning, and natural language processing—to address the limitations of conventional test automation. The research also highlights the evolution from rule-based testing to intelligent, self-healing, and autonomous testing frameworks.Quantitative comparisons between traditional and AI/ML-driven testing approaches reveal substantial improvements in test efficiency, coverage, defect detection accuracy, and maintenance costs. Graphs and tables included in this study illustrate the performance gap and adoption trajectory across industries, emphasizing a projected surge in AI-integrated testing solutions by 2030.Furthermore, the paper outlines key implementation challenges, including data dependency, skill shortages, and integration complexity, and offers strategic recommendations to overcome them. By providing a structured roadmap for organizations, this research not only evaluates the current landscape but also forecasts future innovations such as generative test case creation, digital twins for testing, and fully autonomous test agents.The findings establish that AI/ML is not merely enhancing software test automation—it is redefining its very foundations. The fusion of intelligent algorithms with testing workflows promises a paradigm shift toward faster releases, higher software quality, and sustainable testing practices for the next generation of software engineering.